Postbiotic Activity of Enterococcus asini EAs 1/11D27 Strain Originating from the Norik of Muráň Breed - Andrea Lauková; Eva Styková; Valentína Focková; Aleksandra Troscianczyk; Marián Maďar (International Journal of Equine Science, 2024)
The Norik of Muráň breed is a Slovak horse breed mainly intended for forestry and agriculture-related work. It is also a unique type among the cold-blooded horse breeds. In general, the microbiota influences animal health status. However, limited information regarding the microbiota of this horse species is available. Similarly, few aspects are known about the species Enterococcus asini bacteriocin (postbiotic) potential. Therefore, this study investigated the E. asini strain EAs 1/11D27, isolated from mucosal samples obtained from horses, along with the evaluation of its molecular characteristics and bacteriocin (postbiotic) activity. Taxonomic allocation of the strain EAs 1/11/D27 was confirmed using the sequencing method, reaching 99.86% similarity (match) with the nucleotide sequence of the strain E. asini NR113929.1. E. asini EAs 1/11D27 has been assigned the GenBank accession number (AN) MN822908. This strain is hemolysis-negative, deoxyribonuclease-negative, and gelatinase-negative. EAs 1/11D27 lacks genes encoding for virulence factors such as gelatinase, enterococcal surface protein, adhesins, hyaluronidase, and aggregation substance. It does not produce damaging enzymes and is susceptible to antibiotics. Additionally, it produces bacteriocin-like substances with inhibitory activity against 165 out of 170 indicator bacteria tested (97%). The highest inhibitory potential was recorded against staphylococci (88), enterococci (57), lactococci (7), and streptococci (4/8). The growth of 9 out of 10 Gram-negative strains was also inhibited. These results suggest a valuable postbiotic potential of the studied bacteriocin substance, and further studies are needed to establish its applications in horses.